AL-I’JĀZ AL-ṢAUTĪ FĪ AL-QURĀN AL-KARĪM WA NAMĀZIJUH AL-MU‘ĀṢIRAH: DIRĀSAH TĀRĪKHIYYAH TAḤLĪLIYYAH - Ismu Ridha; Abu Zinah, Manshur Mahmud; Subhi, Muhibbul; Syam, Futry (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2024)
Al-Qur’an is the most miracle of the Prophet Muhammad who has a various forms of miracles (wujūh al-i'jāz), one of them is the “Audio Miracle” or al-I'jāz al-Ṣautī. Therefore, this research aims to present and analyze the discourse of i'jāz al-Sautī in the Qur’an. To achieve this, researchers use a historical approach by studying the history of the revelation of the Qur’an and its transmission to humanity, then this research uses an analytical approach to several examples of verses containing i'jāz al-Sautī in a contemporary perspective, and finally, the research uses an istinbāṭi approach, namely formulating a study in conclusion form. This research obtained several findings, First, I'jāz al-Sautī is the most visible form of i'jāz of the Qur’an, because it can be felt by all readers and listeners, not only limited to Arabs, but for all humans. Second, i'jāz al-Sautī is an important form of i'jāz which was initially conveyed from Allah to Jibril as. and then to the propet Rasulullah using the oral voice method (musyāfahah). Third, among the secrets of the i'jāz al-Sautī is the beautiful and detailed arrangement between the harmony of the sounds that provide comfort and tranquility for the soul and the harmony of the meaning contained therein. Fourth, Umar bin Khattab’s islamic event is the most obvious proof of the influence of the sound of the sentences of the Qur’an on the soul of the listener.